Analisis Pengaruh Motivasi Kerja Terhadap Kepuasan Kerja Karyawan Pada Restoran Bebek Sawah Pattimura Padang - Afif Riskiansyah; Azariah Azariah; Chinta Salsabilla; Andry Novrianto (CV. ITTC INDONESIA, 2025)
This study aims to analyze the effect of work motivation on employee job satisfaction at Bebek Sawah Pattimura Padang Restaurant. Work motivation is one of the important factors that influences the level of employee job satisfaction, which ultimately has an impact on individual performance and organizational success. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 90 restaurant employees as respondents. Data analysis was carried out using a simple linear regression method to test the relationship between work motivation variables (independent variables) and job satisfaction (dependent variables). The results of the study indicate that work motivation has a positive and significant effect on employee job satisfaction. This is evidenced by the results of the t-test which shows a significant value below 0.05. This study concludes that increasing work motivation, either through incentives, a conducive work environment, or awards for achievement, can increase employee job satisfaction. The implications of this study are expected to be input for the management of Bebek Sawah Pattimura Padang Restaurant in formulating strategies to increase work motivation to create a more productive work environment. Keywords: Work Motivation, Job Satisfaction, Employees, Restaurant